ULK1: a promising biomarker in predicting poor prognosis and therapeutic response in human nasopharygeal carcinoma. - Miao Yun; Hai-Yan Bai; Jia-Xing Zhang; Jian Rong; Hui-Wen Weng; Zhou-San Zheng; Yi Xu; Zhu-Ting Tong; Xiao-Xia Huang; Yi-Ji Liao; Shi-Juan Mai; Sheng Ye; et al. (PLoS ONE, 2015)
Plenty of studies have established that dysregulation of autophagy plays an essential role in cancer progression. The autophagy-related proteins have been reported to be closely associated with human cancer patients' prognosis. We explored the expression dynamics and prognostic value of autophagy-related protein ULK1 by immunochemistry (IHC) method in two independent cohorts of nasopharygeal carcinoma (NPC) cases. The X-tile program was applied to determine the optimal cut-off value in the training cohort. This derived cutoff value was then subjected to analysis the association of ULK1 expression with patients' clinical characteristics and survival outcome in the validation cohort and overall cases. High ULK1 expression was closely associated with aggressive clinical feature of NPC patients. Furthermore, high expression of ULK1 was observed more frequently in therapeutic resistant group than that in therapeutic effective group. Our univariate and multivariate analysis also showed that higher ULK1 expression predicted inferior disease-specific survival (DSS) (P<0.05). Consequently, a new clinicopathologic prognostic model with 3 poor prognostic factors (ie, ULK1 expression, overall clinical stage and therapeutic response) could significantly stratify risk (low, intermediate and high) for DSS in NPC patients (P<0.001). These findings provide evidence that, the examination of ULK1 expression by IHC method, could serve as an effective additional tool for predicting therapeutic response and patients' survival outcome in NPC patients.